Hypatia of Alexandria: Feminisme dan Peran Simbolis Perempuan dalam Mengembangkan Ilmu Pengetahuan: Hypatia of Alexandria: Feminism and the Symbolic Role of Women in Developing Science - Fitria, Fitria (Jurnal Filsafat Indonesia, 2024)
The Hypatia of Alexandria was an expert in philosophy, mathematics, and astronomy during the ancient Roman civilization. Her figure epitomizes an intelligent, resilient, and brilliant woman. The increasing dominance of religious influence during Hypatia's era strengthened, gradually sidelining the scientific knowledge she initially disseminated. Hypatia's role in building civilization through the advancement of knowledge eventually came to a halt when she was deliberately murdered by a highly fanatic group adhering to Church teachings and the Christian religion. Hypatia's life in the ancient Roman civilization portrays the conflict between science and the interests of certain parties. Regardless of the significant influence of women in developing scientific knowledge, if the truth embraced by others is fanatical and disregards existing facts, knowledge becomes futile. This article discuses Hypatia's journey and role in building civilization in ancient Roman times through the development of scientific knowledge while examining Hypatia's character from a feminist perspective. The research methodology employed is a literature review. The researcher conducted a search for relevant journal articles through Scopus and Google Scholar. Keywords entered into the search engine include "Hypatia of Alexandria"; Hypatia AND Philosophy; Hypatia AND Feminism; Hypatia AND Knowledge. Hypatia played a significant role in building the civilization of knowledge in ancient Roman times, proving that the role of women in building civilization through the development of scientific knowledge is a notable